2014
DOI: 10.1111/1467-8500.12080
|View full text |Cite
|
Sign up to set email alerts
|

From Accountability to Assurance – Stakeholder Perspectives in Local Government

Abstract: This article reports on research which sought to explore the understanding of accountability for performance amongst constituents of local government in Western Australia. Recent trends to increase the public accountability and financial reporting requirements for local governments underline the need to understand the value and use made of this performance information by local government constituents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…Effectiveness measures for public accountability deal with what was achieved – outcomes rather than outputs – making data collection and calibration more complex (Kloot, 1999; Dollery and Wallis, 2001a; Kluvers and Tippett, 2011). Examples include measures to assess service importance (Breitbarth et al , 2010), reward structures, training, teamwork and innovation (Baird et al , 2012), and better connecting accountability to quality assurance (Quinlivan et al , 2014). In addition, practitioners strive to develop better measures of social value, for example: Using social capital research, Brunetto and Farr-Wharton (2008) identified how ambiguous roles and misunderstandings about customer NPM accountability surfaced from a variety of communicative competencies and processes, such as the quality of social interactions, internal and external information-sharing and needs analyses determined during community consultations. Siriwardhane and Taylor (2017) adopted stakeholder salience , asking who is important and how should such needs be prioritised?…”
Section: Contextualised Themes On Performance Measurement: Discussionmentioning
confidence: 99%
“…Effectiveness measures for public accountability deal with what was achieved – outcomes rather than outputs – making data collection and calibration more complex (Kloot, 1999; Dollery and Wallis, 2001a; Kluvers and Tippett, 2011). Examples include measures to assess service importance (Breitbarth et al , 2010), reward structures, training, teamwork and innovation (Baird et al , 2012), and better connecting accountability to quality assurance (Quinlivan et al , 2014). In addition, practitioners strive to develop better measures of social value, for example: Using social capital research, Brunetto and Farr-Wharton (2008) identified how ambiguous roles and misunderstandings about customer NPM accountability surfaced from a variety of communicative competencies and processes, such as the quality of social interactions, internal and external information-sharing and needs analyses determined during community consultations. Siriwardhane and Taylor (2017) adopted stakeholder salience , asking who is important and how should such needs be prioritised?…”
Section: Contextualised Themes On Performance Measurement: Discussionmentioning
confidence: 99%
“…Bisa saja korupsi terjadi pada kondisi yang rasio keuangan pemerin tah daerahnya baik, dan sebaliknya juga ko rupsi bisa terjadi pada kondisi rasio keuang an daerah buruk. Temuan ini konsisten dengan hasil studi , Heriningsih & Marita (2013), dan Quinlivan, Nowak, & Klass (2014) yang mengungkap kan bahwa kinerja keuangan berdasarkan indikator kemandirian, rasio aktivitas, dan rasio pertumbuhan tidak memiliki dampak pada jumlah korupsi di pemerintah daerah. Terjadinya korupsi di suatu daerah mung kin saja disebabkan oleh faktor lain baik secara individu maupun institusi, seperti tingkat moralitas yang rendah serta tidak adanya pengawasan yang ketat menyebab kan peluang korupsi menjadi lebih besar.…”
Section: Hasil Dan Pembahasanunclassified
“…The absence of data generated by PWF networks themselves—so‐called metadata associated with network use—is a gap in our evidence base. As we discuss below, the difficulty of accessing network metadata not only highlights a methodological challenge for researchers in this relatively new field of inquiry, it raises long‐standing questions of transparency and accountability in public administration, a persistent theme in this journal (Argyrous, ; Carnegie, ; Quinlivan, Nowak, & Klass, ; Stafford & Stapleton, ).…”
Section: Methodsmentioning
confidence: 99%